Travel Story (2012)
Jessica Serna is a student of Social Communication and has been a workshopist at EAFIT Children's University for two years. In 2012 he worked on Encounters with the Question, and on the Routes of Economy and Business and Society and Cultures. On this occasion we wanted to know what this experience, which describes as a journey, has meant to her.